The legal framework of the International Committee of the Red Cross in the protection of women and children (Journal of the College of Basic Education, 2022)
The International Committee of the Red Cross carries out large and important tasks at the global level and in various countries, and that the work of the International Committee of the Red Cross in the field of humanitarian protection, including the protection of women and children in international and non-international conflicts, must be attributed to legal rules and work within the framework of these international legal rules And the Ministry of the Interior to help the International Committee to carry out its tasks, otherwise the actions carried out by the International Committee of the Red Cross are considered illegal.